Relationship between Cluster of Differentiation 4 (CD4) Levels and the Occurrence of Depression in People Living With HIV/AIDS at Ngoerah Hospital Denpasar - Qurrota Aini; Ida Aju Kusuma Wardani; Anak Agung Yuli Gayatri; I Wayan Gede Artawan Eka Putra; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani; Ni Ketut Putri Ariani; I Komang Ana Mahardika (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Depression is the most common psychiatric complaint associated with HIV/AIDS patients. The depression rate in HIV/AIDS patients is twice as high as in the general population. The issue of depression in people with HIV/AIDS requires serious attention as it can have a broad impact on their health and lives. The lower Cluster Differentiation 4 (CD4) counts in People Living with HIV/AIDS (PLWHA) can be an indicator of depression. This study aims to determine the relationship between CD4 levels and the occurrence of depression in PLWHA. Method: Analytical observational study with a case-control design. Sampling was done using simple random sampling at the VCT Polyclinic of Ngoerah Hospital Denpasar and involved structured interviews using the Hamilton Depression Rating Scale (HDRS) questionnaire. CD4 levels were obtained from medical records to establish a relationship with depression. The study included 72 subjects, consisting of 36 in the depression group and 36 in the control group. Data analysis included variable descriptions, bivariate analysis, and multivariate analysis using logistic regression. Results: The results of this study indicate a relationship between CD4 levels <200 and the occurrence of depression (p < 0.001) with an Adjusted Odds Ratio (AOR) of 14.968 and a Confidence Interval (CI) of 3.646 – 61.446. Conclusion: There is a relationship between CD4 levels <200 and the occurrence of depression in patients with HIV/AIDS.